Relative idiosyncratic volatility and the timing of corporate insider trading - Gider, Jasmin; Westheide, Christian (Journal of Corporate Finance, 2016)
This paper investigates whether corporate insiders trade when asymmetric information is high, using data on U.S. corporate insider transactions between 1986 and 2012. We generalize the literature focusing on insider trading around the announcement of different categories of corporate events. The key innovation of this paper is our asymmetric information proxy relivol, which measures deviations of idiosyncratic volatility from a firm's normal level. Our findings suggest that relivol positively predicts insider purchases, indicating that insiders buy shares when their informational advantage is high. However, insiders appear to sell less when relivol is high, which is consistent with existing evidence on sales being driven by alternative, non-information-related trading motives such as liquidity or diversification needs. Furthermore, we find that profits are significantly higher when insiders buy during periods of high relivol but not when they sell shares.